A Critique of Hans-Hermann Hoppe’s Thesis on Lesser Harmfulness of Monarchy than Democracy - Sierpiński, Jacek (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
The aim of this paper is to critically analyse the thesis of Hans-Herman Hoppe that although any government – taken as a territorial monopolist in the field of jurisdiction and tax imposition – is an organisation harmful both from the economic and ethical point of view since it violates property rights in an institutionalised and legal manner, exploiting private owners and contributing to the process of “decivilization,” yet the monarchy is less harmful than any democratic state. The ultimate point is to prove that Hoppe’s assumption on lower time preference of the governing monarch is not sufficient to conclude that monarchy is less responsible for violating property rights and that it contributes to the process of “decviliziation” less than democracy.